Robust Image Hashing Scheme using Laplacian Pyramids. (June 2020) - Hamid, Hira; Ahmed, Fawad; Ahmad, Jawad
Abstract: Due to tremendous growth in multimedia applications and services, people can easily create, distribute, broadcast and store information. The fact that multimedia content can be easily copied and tampered has motivated a large number of researchers to devise image verification techniques using perceptual image hashing. In this paper, a perceptual image hashing technique is proposed by using difference of Laplacian pyramids. A Laplacian pyramid is a multi-scale representation of an image and can be used to extract stable features. In the proposed scheme, two different pyramids are generated by using filters of different diameters. The difference of Laplacian is calculated to get a unique and robust hash. A number of experiments have been carried out to gauge the effectiveness of the proposed scheme. The results reveal that the proposed technique is robust against non-malicious manipulations and can detect minute level tampering.